Learning Effectiveness and Level of Motivation Following Educational Technology Learning During Pandemic to State High School Students in Banyuwangi Regency - Fuad Qohar; Anung Priambodo; Achmad Widodo (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This research generally aims to determine the effectiveness of learning and motivation to participate in high school student learning during the pandemic in physical education subjects. The research was conducted on public high school students in Banyuwangi Regency. In this case, the sample is 1,061 students, divided into 529 students in independent regional schools and 532 students in developed regional schools. This research is a quantitative descriptive study by obtaining data from questionnaires distributed to students. Students who fill out a random questionnaire in two schools that have been selected in the independent region and two schools selected in the developed region. Based on this research data, the learning effectiveness of public high school students in independent areas in Banyuwangi Regency is in the "good" category with an average value of 2.58. Meanwhile, in developed areas, the learning effectiveness of State Senior High School students in Banyuwangi Regency is in the "medium" category with an average value of 2.50. Data on motivation to participate in the learning of state high school students in independent areas in Banyuwangi Regency is in the "high" category with a percentage of 53.31% of the sample. Meanwhile, in the advanced regions, the motivation for participating in the learning of State Senior High School students in Banyuwangi Regency is also included in the "high" category with a percentage of 59.21% of the sample.